THE RELATIONSHIP BETWEEN WORKLOAD AND NURSES' PERFORMANCE IN DOCUMENTING NURSING CARE AT CIMALAKA PUBLIC HEALTH CENTER, WEST JAVA - Citra Nurhasanah, Dewi; Sutresna, Iyos; Ridwan, Heri (Buletin Veteriner Udayana, 2024)
Nurses' workload is related to patient care and service and can be measured by the length of working hours and the number of patients treated and can affect a nurse's performance. One of the standards of nurse performance in a health institution is to document nursing care. The purpose of this study was to determine the relationship between workload and nurse performance in documenting nursing care at the Cimalaka Health Center. The type of research used in this study was quantitative with a descriptive correlation design. The sampling technique used total sampling with 20 respondents. Data analysis used parametric statistical tests, namely Pearson Product Moment using SPSS software. Based on the results of the data obtained, 12 nurses felt they had a moderate workload and 13 nurses were in the good performance category. It can be concluded that there is a significant relationship between workload and nurse performance in documenting nursing care at the Cimalaka Health Center with a p-value of 0.028 (p <0.05). It is expected to maintain good performance in documenting nursing care so that it can provide quality services.